Service Transformation and Its Impact on Marketing: A Comparison Between Service Logic and Service-Dominant Logic - Zainul Wasik; S. Sudarnice2 Sudarnice; Suwandi S. Sangadji (PT. Mawadaku Sukses Solusindo, 2025)
The purpose of this conceptual piece is to investigate the consequences of the service viewpoint within the framework of marketing. This article uncovers direct and indirect marketing consequences through a conceptual study of two ways to understanding the service perspective: Service Dominant Logic (SDL) and Service Logic (SL). Value co-creation is conceptualised by SDL as a process in which the company, customers, and other stakeholders work together to create value for the customers. The company is in charge of this strategy, and the service provider is essential to creating value. The idea of co-creation may become mired in metaphor, and the management implications of SDL are not only dependent on the service viewpoint. On the other hand, SL provides an analytical method together with the co-creation idea that has the potential to drastically transform marketing from a service standpoint. The customer is the one who drives value creation in the customer process. This research yields eleven management principles of SL, which have the potential to transform marketing through their theoretical and practical implications. Researchers and managers may focus their attention on the intricate process of value generation by using SDL. Meanwhile, SL can analyze this process at the managerial level, to derive opportunities for customer-focused and service perspectives to revolutionize marketing. The resulting analysis and principles help marketing to move beyond simply offering a value proposition and become the responsibility of the entire organization. Beyond traditional marketing, companies must adopt service-influenced marketing and instill a customer-focused mindset in all staff members. New customer-centric and service-influenced marketing strategies may be discovered by academics and managers thanks to the service viewpoint in business, which also has significant management consequences.